Engineering synthetic hydrogel microenvironments to instruct stem cells - Guvendiren, Murat (2013)
Advances in our understanding and ability to manipulate stem cell behavior are helping to move stem cell-based therapies toward the clinic. However, much of our knowledge has been gained from standard 2-dimensional culture systems, which often misrepresent many of the signals that stem cells receive in their native 3-dimensional environments. Fortunately, the field of synthetic hydrogels is developing to better recapitulate many of these signals to guide stem cell behavior, both as in vitro models and as delivery vehicles for in vivo implantation. These include a multitude of structural and biochemical cues that can be presented on the cellular scale, such as degradation, adhesion, mechanical signals, topography, and the presentation of growth factors, often with precise spatiotemporal control.